Timmy loves football - Geatches, Hazel (United Kingdom : Aardman Animations limited, 2021)
Timmy and his friends play football.
"Timmy Loves Football" likely tells a simple story about the character Timmy from Timmy Time and his enjoyment of playing football (soccer). The book probably uses basic language and concepts suitable for beginner English readers, focusing on themes of play and sports. Location: 2A
Keywords: Timmy loves football book